Variable grammars are variable across registers: future temporal reference in English. (October 2022) - Engel, Alexandra; Szmrecsanyi, Benedikt
Abstract: It is widely accepted that internal constraints on variation are not modulated by social and stylistic factors (e.g., Labov, 2010 :265). Is this also true for register differences as a special type of sociostylistic factor? To address this question, we investigate future temporal reference (FTR) variation in English ( It'll be fun versus It's gonna be fun ) via a variationist corpus study ( n = 2, 600 tokens) and a supplementary rating experiment ( n = 114 participants) across four broad registers: conversations, parliamentary debates, blogs, and newspaper prose. Multivariate analysis of the corpus dataset indicates that register modulates the effect of five out of nine internal constraints, suggesting that variable grammars vary considerably across registers. The experiment confirms that language users are indeed sensitive to, and aware of, the register-specificity of how variation is conditioned. We conclude by discussing the implications of our findings for variationist sociolinguistics and for variational linguistics in general.